2003
DOI: 10.1046/j.1423-0410.2003.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of six blood donors highlights the complementary role and limitations of hepatitis C virus antibody and nucleic acid amplification tests

Abstract: This study demonstrated that at least five of six HCV NAT yield donors were in the pre- or early antibody seroconversion phase of infection. The observation that one yield donor demonstrated HCV RNA that fluctuated above and below the limit of detection of the primary NAT-screening assay supports the maintenance of both NAT and antibody screening for HCV. Follow-up testing of suspected yield donors revealed that the primary and alternate anti-HCV immunoassays had different performance characteristics, dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…However, a concern of nondetected HCV viremia exists in patients who have negative PCR results but S/Co ratio >11. It is known that HCV RNA may not be detectable in some patients during the acute phase of their diseases, and intermittent HCV RNA positivity has been observed among persons with chronic HCV infection . Thus, we suggest that for patients with negative PCR and S/Co ratio >11, PCR should be repeated in 6 months to rule out active HCV infection.…”
Section: Discussionmentioning
confidence: 96%
“…However, a concern of nondetected HCV viremia exists in patients who have negative PCR results but S/Co ratio >11. It is known that HCV RNA may not be detectable in some patients during the acute phase of their diseases, and intermittent HCV RNA positivity has been observed among persons with chronic HCV infection . Thus, we suggest that for patients with negative PCR and S/Co ratio >11, PCR should be repeated in 6 months to rule out active HCV infection.…”
Section: Discussionmentioning
confidence: 96%
“…The finding of a c22 band in RIBA may be highly indicative of previous HCV exposure, [12][13][14][15] and donors with this serologic profile should probably be excluded even in spite of a subsequent seroreversion to RIBA negative.…”
Section: Discussionmentioning
confidence: 99%
“…Hyland et al . [8] followed up six NAT‐positive, serology‐negative (Abbott HCV PRISM) donors and found that three were actually reactive with Murex HCV EIA and also reactive for c22 in the RIBA‐3 immunoblot. Of the remaining three donors, one developed antibodies to c100 and c33 in RIBA‐3, similarly to our donor, and eventually lost NAT reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirms their finding and also that of Hyland et al . [8], that, in certain individuals, transient periods with low levels of viral RNA concentrations can occur around seroconversion. Fang's donor would have remained undetected on day 56 if screened using the normal donor‐screening tests.…”
Section: Discussionmentioning
confidence: 99%